Digestibility of diets containing calcium salts of fatty acids or soybean oil in horses1. Issue 2 (7th January 2020) - Fehlberg, Laura K; Lattimer, James M; Vahl, Christopher I; Drouillard, James S; Douthit, Teresa L
Abstract: Calcium salts of fatty acids (CSFAs) frequently are fed to ruminants, but their fate in the equine digestive system is unknown. The purpose of this study was to compare Enertia s/f, a proprietary CSFAs, and soybean (SB) oil with respect to impact on apparent total tract nutrient digestion and cecal fermentation parameters in horses. Eight cecally cannulated Quarter Horses were used in a crossover design in which horses consumed a diet for 32 d consisting of 1.5% body weight (BW) (as-fed) smooth bromegrass hay and 0.5% BW (as-fed) pelleted concentrate containing 4.9% CSFAs or 4.1% SB oil. Fecal samples were collected every 4 h from day 30 to 32 of each period and analyzed for apparent total tract digestibilities of dry matter (DM), neutral detergent fiber (NDF), acid detergent fiber (ADF), crude protein (CP), crude fat (CF), and gross energy (GE) using acid detergent insoluble ash as an internal marker. Cecal digesta was obtained at 0, 2, 4, 6, 8, 10, and 12 h following the morning meal on day 29 of each period and analyzed for pH and concentrations of volatile fatty acid (VFA) and long-chain fatty acids (LCFAs). Serum was collected on day 33 of each period following a 16-h fast and analyzed for triglycerides and cholesterol. Apparent total tract digestibilities of DM, NDF, ADF, CP, CF, and GE were unaffected by lipid source ( P > 0.10). Serum triglycerides tended to be greater in horses consuming CSFAs compared to SB ( P = 0.10); however, serum cholesterol was not different ( P = 0.45). In horses consuming SB, cecal pH decreased below baseline (hour 0) at hours 2, 4, and 6 ( P < 0.01), whereas cecal pH in horses consuming CSFAs was below baseline at hours 4 and 6 ( P < 0.01). There were no treatment or time effects on cecal pH ( P > 0.10). Cecal concentrations of total VFAs were greater in horses consuming SB compared to CSFAs at hour 2 ( P = 0.01). Cecal concentrations of acetate, propionate, acetate:propionate (A:P), and butyrate were affected by time ( P < 0.01). Propionate was less at hour 2 in horses fed CSFAs compared to horses fed SB ( P = 0.04). A treatment × time interaction was detected for total cecal LCFAs concentration ( P < 0.01); LCFAs concentration was greater at hour 2 for horses consuming CSFAs compared to horses fed SB ( P = 0.02). SB oil and CSFAs have similar effects on the digestion of DM, NDF, ADF, GE, CF, and CP.